Ferroelectric Polarization Enhancement in Hafnium-Based Oxides Through Capping Layer Engineering - Hsuan-Han Chen; Ruo-Yin Liao; Wu-Ching Chou; Hsiao-Hsuan Hsu; Chun-Hu Cheng; Ching-Chien Huang (IEEE Journal of the Electron Devices Society, 2022)
In this work, we investigate that the capping layer (CL) engineering of aluminum oxide (AlOx) on the dopant-free hafnium oxide (HfOx) and the hafnium zirconium oxide (HfZrOx) ferroelectric metal-ferroelectric-metal (MFM) capacitors. The AlOx CL featuring large bandgap and excellent thermal stability offers a stable interface favorable for ferroelectric phase transition. Therefore, the ferroelectric polarization and high-temperature leakage current of HfZrOx MFM capacitor can be largely improved due to the combination of zirconium doping and AlOx capping effect. From the analysis of interface thermodynamic stability and leakage current mechanism, the AlOx CL effectively alleviates interface defect traps between electrode and ferroelectric HfZrOx, which lowers high-temperature leakage current, reduces ferroelectric domains pinning, enhances ferroelectric polarization, and stabilizes the long-term endurance cycling.